Comparison of nalbuphine versus fentanyl as intrathecal adjuvant to bupivacaine for orthopedic surgeries: A randomized controlled double-blind trial - Ankit Sharma; Sujata Chaudhary; Mahendra Kumar; Ruchi Kapoor (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Intrathecal adjuvants are used with local anesthetics to prolong the duration and provide postoperative pain relief while minimizing the dose of local anesthetic. Nalbuphine is an agonist-antagonist opioid and provides prolonged duration of analgesia with fewer side effects of fentanyl such as pruritus, nausea, and vomiting. The aim of this study was to evaluate and compare the onset and duration of sensory and motor blockade, hemodynamic effects, duration of postoperative analgesia, and adverse effects of nalbuphine and fentanyl given intrathecally with hyperbaric 0.5% bupivacaine in orthopedic lower limb surgeries. Material and Methods: Sixty six patients classified in American Society of Anesthesiology (ASA) classes I and II scheduled for orthopedic lower limb surgeries were enrolled. Patients were randomly allocated to receive 15 mg of hyperbaric bupivacaine with either 1 mg nalbuphine (group N), 25 μg fentanyl (group F) or 0.9% normal saline (group C) intrathecally. Results: Patients who received intrathecal nalbuphine (group N) had a significantly delayed onset of sensory and motor block as compared to patients who received fentanyl (group F). The time to two segment regression was significantly prolonged in group F (122.05 ± 10.65 minutes) as compared to group N (114.55 ± 10.90 minutes) [P < 0.05]. The mean duration of motor blockade was significantly prolonged in group F (197.73 ± 15.09 minutes) as compared to group N (180.68 ± 15.68 minutes) [P < 0.05]. Duration of spinal analgesia was comparable in group N (323.18 ± 57.39 minutes) and group F (287.05 ± 78.87 minutes), both significantly more than group C (224.32 ± 42.54 minutes). Hemodynamic effects, 24-h rescue analgesic requirements, and incidence of side effects were comparable among group N and F. Conclusion: Intrathecal nalbuphine in a dose of 1 mg is an equally useful alternative to fentanyl in a dose 25 μg when used as an intrathecal adjuvant to bupivacaine for lower limb surgeries. The prolonged duration of analgesia and no adverse effects makes it a good choice for the orthopedic procedures of lower limb.